2013
DOI: 10.33549/physiolres.932541
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Study of Radioprotective Effect of NO-Synthase Inhibitors and Acetyl-L-Carnitine

Abstract: This study investigated the protective effect of two nitric oxide synthase inhibitors Nω-nitro-L-arginine methyl ester (L-NAME, 100 mg/kg i.p.) and aminoguanidine (AG, 400 mg/kg i.p.), and an antioxidant acetyl-L-carnitine (ALC, 250 mg/kg i.p., once daily for five days) against radiation-induced damage in Wistar rats. Blood samples were collected 6 h after whole-body irradiation with 8 Gy. Plasma concentrations of nitrite+nitrate (NOx) and malondialdehyde (MDA) were measured by high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Moreover, studying the antioxidant role of LC on reduction of radiotherapy-induced complications in various tissues such as brain, liver, and retina showed that using LC before or after radiotherapy significantly decreased the level of MDA and ROS and improved GSH and CAT levels. [59][60][61] Our results revealed that CAT significantly increased in diabetic groups treated with LC versus untreated diabetic group. Oxidation of biological molecules can be induced by hydroxyl (OH À_ c ) radicals generated by hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 48%
“…Moreover, studying the antioxidant role of LC on reduction of radiotherapy-induced complications in various tissues such as brain, liver, and retina showed that using LC before or after radiotherapy significantly decreased the level of MDA and ROS and improved GSH and CAT levels. [59][60][61] Our results revealed that CAT significantly increased in diabetic groups treated with LC versus untreated diabetic group. Oxidation of biological molecules can be induced by hydroxyl (OH À_ c ) radicals generated by hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, pre-treatment with ALC (250 mg/kg, i.p.) of rats prevented the radiation-induced increase in plasma MDA [177]. From the data presented above it is clear that LC and ALC have antioxidant protective effect against oxidative stress caused by irradiation.…”
Section: Antioxidant Effects Of Carnitine Against Oxidative Stress In Vivo: Established Clinical Modelsmentioning
confidence: 75%
“…It was found that L-carnitine had an effect on the recovery of sciatic nerve function as well as enhancing nerve regeneration and suppressing injury-induced degeneration in the nerve axon and its myelin sheath. Wilson et al [68] and Babicova et al [7] explained that L-carnitine blocked the cell death pathway at the mitochondrial level by limiting reactive oxygen species synthesis in addition to reducing the nitric oxide and nitric oxide synthase levels.…”
Section: Discussionmentioning
confidence: 99%